The Influence of Corporate Culture and Leadership on the Performance of Permanent Employees at the Budi Luhur STIKes, Cimahi City - Silvi Faujiah; Ayi Muhiban (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted on permanent employees at the Budi Luhur STIKes, Cimahi City. The purpose of this study was to find out how much the influence of corporate culture and leadership in a company contributes to the performance of permanent employees either partially or simultaneously at STIKes Budi Luhur, Cimahi City. The research method used in this research is descriptive method and associative method. In this study, the unit of analysis is the individual, namely permanent employees at the Budi Luhur STIKes Cimahi City. This study used a saturated sample because all members of the population were selected as samples, namely all permanent employees at the Budi Luhur STIKes Cimahi City as many as 40 respondents. The data collection technique uses a questionnaire. The analytical method uses multiple linear regression analysis, Besides that, the validity and reliability of the research instruments were also tested. Based on the results of the study, it shows that there is an influence both partially and simultaneously on exogenous variables (corporate culture and leadership) on endogenous variables (employee performance). The implication of this research is that the Budi Luhur STIKes can review the guidelines regarding the implementation of tasks and clear directions regarding the implementation of the assigned tasks and increase the sense of employee ownership of the institution to increase employee responsibility for their work